CARCINOMA HEPATIS AND BLOOD GROUP AFFILIATION: CARCINOMA HEPATIS AND BLOOD GROUP AFFILIATION - Todorov, Velislav; Georgiev, Volodia; Boycheva, Maria; Minkov, Cvetan; Georgieva, Rada; Boichev, Milen (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The article discusses the results of a study of 94 patients (72 male and 22 female) suffering from Ca hepatis. The connection between the condition and the blood group affiliation according to the ABO systems and the Rhesus factor is traced. A comparison with the control group of healthy Bulgarian population reveals a significant increase (р<0,01) in the number of patients with blood type A, and a smaller increase in AB blood type. A decrease in the number of patients is seen in the other groups, especially group 0 (р<0,01). The studies show that male patients predominate (3,23 times more than the female)), which supports the findings of previous documented research. In the Rh system the values are almost equal to those of the control group. We assume that belonging to blood type A might be one of the risk factors in the development of Ca hepatis.